Nuclear factor kappa b genetic polymorphisms and association with colorectal cancer susceptibility risk in malaysian population - A molecular epidemiology study - Shafi’i, Mohd Suza1ri Mohd (2013)
Sporadic colorectal cancer (CRC), the most common gastrointestinal malignancy in Malaysia and one of the most common cause of cancer deaths, is a major public health problem. CRC is a multifactor caused disease resulting from complex interaction between environmental and genetic predisposition factors. However, the genetic predisposition risk of an individual for CRC development remains largely undetermined. Recently, Nuclear Factor kappa B signalling pathway has been implicated in colorectal carcinogenesis. Given the important role of NFkB signalling pathway in CRC development, it was hypothesized that genes and genetic variations in NFkB signalling pathway could be putative genetic predisposition factors. This case-control study was designed to test this hypothesis. The objectives were to investigate the genotype and allele frequencies of three SNPs, namely A to G variation at 3’ UTR of NFKBIA, -519 C to T of NFKBIA and -94 insertion/deletion ATTG of NFKB1 gene in Malaysian CRC patients and normal controls and to determine the risk association of these three SNPs with CRC predisposition. This case-control study involved 474 study subjects with 237 histophatologically confirmed CRC patients as cases and 237 normal healthy volunteers as controls. After getting informed consent, blood samples from study subjects were collected, DNA extracted and genotyping of the three SNPs was carried out employing Polymerase Chain Reaction - Restriction Fragment Length Polymorphism (PCR-RFLP) technique. Genotypes were categorized into homozygous wildtype, heterozygous and homozygous variant. Risk associations of specific genotypes with CRC susceptibility were determined by deriving Odds Ratio (OR) with corresponding 95% Confidence Intervals (C.I) using unconditional logistic regression. The frequencies of homozygous variant genotype of A to G variation at 3’ UTR of NFKBIA and NFKBI -94 insertion/deletion ATTG polymorphism were significantly higher in CRC patients compared to controls. The frequency of homozygous variant genotype of-519 C to T polymorphism of NFKBIA was very low in the cases and nil in the controls. When analyzed singly, the homozygous variant genotype (GG) of NFKBIA 3’ UTR A to G SNP showed significantly higher risk association with CRC predisposition, whereas the -519 C to T variation of NFKBIA did not show any risk association. Similarly, the homozygous variant genotype (ins/ins) of NFKBI -94 insertion/deletion ATTG SNP showed significantly higher risk association with CRC predisposition when analyzed singly. In the two SNP combination analysis, the genotype combinations of NFKBIA - 519 C to T (CC) / A to G variation at 3’ UTR of NFKBIA (AG) genotypes, NFKBIA - 519 C to T (CC) / A to G variation at 3’ UTR of NFKBIA (GG) genotypes, NFKBIA - 519 C to T variation (CC) / NFKBI -94 insertion/deletion ATTG polymorphism (ins/ins) genotype, A to G variation at 3’ UTR of NFKBIA (AG) / NFKBI -94 insertion/deletion ATTG polymorphism (del/ins), A to G variation at 3’ UTR of NFKBIA (GG) / NFKBI -94 insertion/deletion ATTG polymorphism (del/del) and A to G variation at 3’ UTR of NFKBIA (GG) / NFKBI -94 insertion/deletion ATTG polymorphism (del/ins) emerged as high risk genotype combinations associated with CRC predisposition. It is presumed that genetic variation in NFKBIA and NFKBI genes may result in sustained or constitutive activation resulting in incorrect regulation of the associated proteins and thereby contribute to pathogenesis of CRC. The genotype and/or genotype combinations which showed high risk association with CRC could be considered as putative “at risk” predisposition genotypes associated with CRC susceptibility.